Application Values of T-SPOT.TB in Clinical Rapid Diagnosis of Tuberculosis - Feng ZHU; Qinfang OU; Jian ZHENG (Tehran University of Medical Sciences, 2017)
Background: This paper aims to explore the application value of tuberculosis-specific enzyme-linked immunospot assay (T-SPOT.TB) in the diagnosis of tuberculosis. Methods: Fifty one patients with tuberculosis (TB) admitted to Wuxi No.5 People's Hospital, Wuxi, China from June 2015 to June 2017 were selected as the TB group, and 40 patients without tuberculosis admitted in the same period were randomly selected as the non-TB group. Patients in the two groups received T-SPOT.TB, TB antibody (TB-Ab) test and mycobacterium TB deoxyribonucleic acid (TB-DNA) test, and the results were compared. Results: Comparisons of the sensitivity of the three methods showed that the sensitivity of T-SPOT.TB was the highest, followed by TB-DNA from sputum samples, and that of TB-Ab was the lowest. The specificity of TB-Ab was the highest, followed by T-SPOT.TB, and that of TB-DNA from sputum samples was the lowest. In the receiver operating characteristic (ROC) curve analysis, the area under curve (AUC) of T-SPOT.TB (0.896) was the highest, followed by TB-DNA from sputum samples (0.772), and that of sputum smears (0.698) was the lowest. Conclusion: T-SPOT.TB can quickly and accurately determine the presence of tuberculosis infection, and it is a non-invasive examination, which can further assist in the diagnosis and guide the treatment.